A compact CPW-fed ultra wideband antenna with time domain analysis - Kasi B.; Jalil Y.E.; Chakrabaty C.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
A simple and compact Ultra-Wideband (UWB) printed antenna fed by Coplanar Waveguide (CPW) is presented in this article. The proposed antenna occupies only 3035 mm2 space and thickness of 1.575 mm on a substrate of dielectric constant 3.0. The presented structure gives an impedance bandwidth that ranges from 2.8 to 12 GHz for a return loss less than-10 dB. Moreover, a stable radiation pattern with appreciable gain across the UWB band can be obtained. Group delay result shows a linear phase response throughout the band. Transient analysis of the designed antenna indicates stable signal transmission confirming its suitability for short-range UWB impulse radios. 2013 IEEE.